AN ANALYSIS OF FIGURATIVE LANGUAGE IN ALESANA'S ALBUM TRY THIS WITH YOUR EYES CLOSED - Sumigar, Isabela; Andries, Fivy A.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this study was to examine the types and meaning of figurative language present in Alesana's album Try This With Your Eyes Closed. A semantic approach and descriptive qualitative research methods were employed for this analysis. The figurative language theory by Miles and Huberman (1994) guided the data analysis. Data collection was carried out through documentation, which included three steps: listening to the songs, transcribing the lyrics, and highlighting the lyrics containing figurative language. The focus was on three types of figurative language: metaphor, hyperbole, and irony. The results of this study explain how figurative language plays an important role in song lyrics to convey meaning indirectly and add a dramatic impression, there are 23 metaphor, 18 hyperbole and 7 irony, out of the five chosen songs in this album, there are also data that have two figurative language at the same time, for a total of 48 figurative language found. The analysis revealed that metaphors were the most frequently used figurative language in the album's lyrics.